Allelopathic effects of Aizoon canariense leaf leachates on growth, biochemistry, and oxidative stress responses in selected crop species - Alghanem, Suliman M. S. (Frontiers in Plant Science, 2025)
IntroductionAllelopathy offers a promising ecological approach to sustainable weed and crop management, yet the allelopathic potential of many underutilized wild species remains unexplored. Aizoon canariense, a xerophytic plant native to arid regions, may produce bioactive compounds capable of influencing the growth and physiology of neighboring crops. This study aimed to evaluate the chemical composition and allelopathic effects of A. canariense aqueous leaf leachates (LL) on four major crops—wheat (Triticum aestivum), barley (Hordeum vulgare), rapeseed (Brassica napus), and mung bean (Vigna radiata). MethodsThe chemical constituents of A. canariense leaves were identified using gas chromatography–mass spectrometry (GC-MS). Four crops were treated with 10% and 15% LL, and various morphological (shoot/root length, biomass), physiological (chlorophyll, carotenoids), and biochemical parameters (total phenols, flavonoids, DPPH activity, SOD, CAT, H₂O₂, and MDA content) were evaluated. Correlation analysis was performed to assess relationships among stress responses and growth indicators.Results and DiscussionGC-MS analysis revealed 40 compounds, including sesquiterpenes, phytol, patchouli alcohol, and α-cadinol. LL treatments significantly reduced shoot and root growth, pigment content, and biomass in a dose-dependent manner, with rapeseed and mung bean showing the greatest sensitivity. Conversely, LL exposure elevated phenolic and flavonoid levels, antioxidant enzyme activity (SOD, CAT), and oxidative stress markers (H₂O₂ and MDA). Correlation analysis demonstrated strong negative relationships between growth traits and oxidative damage, and positive associations between phenolic accumulation and antioxidant responses. A. canariense leaf leachates exert significant allelopathic effects on crop plants by inducing oxidative stress and activating antioxidant defenses, suggesting the presence of potent phytotoxic compounds. These findings offer new insights into the ecological role of A. canariense and its potential application as a natural bioherbicide or rotation crop component in sustainable agriculture.